Financial Exclusion in Northern Nigeria: A Lesson From the Developed Countries - Tijjani Muhammad; Besar Bin Ngah; Al-Shaghdari Fahd Mohammed Obad (AFEBI Islamic Finance and Economic Review, 2022)
The objective of this paper is to assess the causes of financial exclusion in northern Nigeria, including the reason and causes behind the accessibility to banking services at a competitive and affordable prices. The study adopted Confirmatory Factor Analysis under Structural Equation Modeling using vulnerable group theory (Religiosity and Poverty) and financial literacy theory (Awareness). In this study, the survey method was used, additionally, the stratified sampling technique is applied as it provides richness and accuracy of information from respondents from various stratums. The participants comprised senior, middle and lower classes for the study justification. The finding indicates the positive relationship between Vulnerable Group Theory and Financial Exclusion while Financial Literacy Theory has no relationship as indicated. Therefore, the vulnerability which is consists of Religiosity and Poverty drive as the major causes of Financial Exclusion in Nigeria. The research provided insights and developed a model that indicates the causes of financial exclusion and apparent barriers to better financial services and inclusion in the community and society.  This study's originality shows that have not used such vulnerable group theory and financial literacy theory for justification.